Surgical complications in 2,840 cases of hemorrhoidectomy by Milligan-Morgan, Ferguson and combined techniques - Santos,Guilherme de Almeida (2012)
The analysis of 2,840 cases of hemorrhoidectomy by open techniques of Milligan-Morgan (2,189 cases), Ferguson (341 cases) and mixed (310 cases) in 11,043 patients with hemorrhoidal disease (HD) allowed the following conclusions. The patients' acceptance of surgical indication for hemorrhoidectomy was 25.7%. Hemorrhoidectomy was more common among women (53.8%) than men (46.2%), and more accepted by women (26.5%) than men (24.8%). Hemorrhoidectomy was more common in patients of the fourth (27.7%), fifth (21.9%) and third (21.0%) decades of age. Most patients who agreed to undergo hemorrhoidectomy were those of the second (38.2%), eighth (35.9%) and ninth (34.5%) decades of age. The overall incidence of surgical complications was 3.0% (87 cases): anal stenosis (1.8%), bleeding (0.8%), worsening of anal hypotonia (0.2%), sepsis (0.1%) and systemic complications (0.1%), with no difference among the techniques used. The incidence of surgical complications by Milligan-Morgan technique was 3.0% - stenosis (1.9%), bleeding (1.9%), worsening of anal hypotonia (0.2%) and systemic complications (0.04%). The incidence of surgical complications by Ferguson's technique was 3.5% - stenosis (1.7%), bleeding (0.6%), worsening of anal hypotonia (0.6%) and sepsis (0.6%). And the incidence of surgical complications by mixed techniques was 2.5% - stenosis (1.0%), bleeding (0.3%), worsening of anal hypotonia (0.3%), sepsis (0.3%) and systemic complications (0.3%). The incidence of surgical complications according to gender was 3.0% among women and 3.2% among men, with higher incidence of stenosis in women (2.0%) and hemorrhage in men (1.1%). Surgical complications were more observed in the eighth (5.1%) and seventh (3.8%) decades of age. The incidence of anal stenosis was 1.8%, being 64.0% without hypotonia and 66.0% without anal fissure (66.0%), with annular stenosis as the most common anatomical shape (70.0%). Anal stenosis was more common among women (2.0%) presenting mean age of 38.2 years, with no relation to age decades. The most common technique for anal stenosis was single anotomy without sphincterotomy (46.0%). All cases of anal bleeding had surgical ligation of all hemorrhoidal pedicles, no matter if the bleeding site was found or not.